Plastome-based phylogeny and biogeography of Lactuca L. (Asteraceae) support revised lettuce gene pool categories - Chu, Ran; Xu, Xuemin; Lu, Zhenwei; Ma, Yonggui; Cheng, Han; Zhu, Shixin; Bakker, Freek T.; Schranz, M. Eric; Wei, Zhen (Frontiers in Plant Science, 2022)
This study generated and analyzed complete plastome and internal transcribed spacer (ITS) data of 46 Lactuca species, 13 African endemic (AE) Lactuca species, and 15 species from eight related genera in Lactucinae. The new plastome and nuclear ITS sequences were then used to reconstruct the phylogenetic relationships of Lactuca species. The whole-plastome data were used to estimate divergence time and ancestral area reconstruction of the identified major Lactuca lineages. The results showed that Lactuca species are generally similar in plastome size, Guanine and Cytosine (GC) content, gene structure, and categories, although crop lettuce (Lactuca sativa L.) and its gene pool relatives were found to have one unique pseudogene (ψ ndhF), and accD, atpF, cemA, clpP, and rpl22 showed signs of positive selection. Our phylogenomic analysis demonstrated that Lactuca is monophyletic after excluding Lactuca alatipes Collett and Hemsl and AE Lactuca species. AE Lactuca species are morphologically distinct from core Lactuca lineage and need to be excluded from Lactua. The core Lactuca species most likely originated from Asia-Temperate W ~6.82 Mya and then dispersed globally and formed nine clades. Finally, the lettuce gene pool concept was amended according to the phylogenetic and historical biogeographic analyses. This study revised the circumscription of Lactuca, revealed robust phylogenetic relationships within the genus, and provided insights into Lactucinae phylogeny. The lettuce gene pool species could be used as potential genetic resources for lettuce breeding.